2020
DOI: 10.1097/jsm.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to the Implementation of iSPRINT: A Sport Injury Prevention Program in Junior High Schools

Abstract: Participants in this study reported positive attitudes about implementing iSPRINT, citing evidence strength, adaptability, and constructs related to the organizational setting that contributed to successful implementation. Potential improvements include modifying certain program components, decreasing the number of components, and reducing the equipment required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…In addition, a significant facilitator to the implementation of the programme was knowing that the programme was evidence-based and from a reliable source (an academic institution). 11 This was also reported by the end users of Active & Safe Central, where several participants cited the success of the site due to its foundation in scientific evidence. This was in addition to the resource being accessible.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, a significant facilitator to the implementation of the programme was knowing that the programme was evidence-based and from a reliable source (an academic institution). 11 This was also reported by the end users of Active & Safe Central, where several participants cited the success of the site due to its foundation in scientific evidence. This was in addition to the resource being accessible.…”
Section: Discussionmentioning
confidence: 74%
“…10 11 For example, a recent study reported both facilitators and barriers to implementing an evidence-based, neuromuscular training programme adapted for physical education classes in junior schools in Alberta, Canada. 11 The physical education teachers cited a significant facilitator to the process of implementing the programme was knowledge of the programme being evidence-based; however, barriers to the process included access to resources to support ongoing implementation efforts, in particular having access to tools to support implementing the programme as intended. 11 In addition, teachers cited this need for programme sustainability as well as to increase capacity at an individual level (eg, teachers themselves having the necessary skills and knowledge).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Further understanding of the barriers to the use of strength, balance and agility exercises in a warm-up program in youth rugby should be explored in future research. In a school setting, barriers identified may include lack of knowledge of their relevance to injury prevention, complexity and time to complete exercise components, and planning required to carry out a NMT warm-up in its' entirety (Richmond et al, 2020 ). Considering the use of strength exercises is important given the intense, collision-nature of rugby and the high physical demands of the sport.…”
Section: Discussionmentioning
confidence: 99%